The Impact of Corporate Governance and Risk Management on Performance and Risk of US Banks - Zheng, Meiqi (2019)
This paper explores how corporate governance and risk management could affect bank performance and risk. In this study, a sample of 84 US banks is examined using the fixed effects model. An integrated set of board and committee characteristics (size, existence and meetings) and various proxies for performance and risk are employed in this paper. The results show that board size is significantly and positively correlated with bank performance and is negatively associated with firm risk. While, board independence is found to have negative impacts on bank performance and risk. Besides, it suggests that board meetings would reduce bank performance and increase risk. The risk management mechanisms (audit committee, risk committee and CRO) seem to have no significant impacts on bank performance and risk. Especially, the effects of risk committees on bank performance and risk appear to be controversial. It implies that the risk management systems in the sample banks require further development.